Macroeconomic adjustment under regime change: From social contract to Arab Spring. (September 2015) - Faria, João Ricardo; McAdam, Peter
Abstract: Against the backdrop of the Arab–Spring protests, we examine macroeconomic stabilization under regime shift. We model this as a dynamic interaction between a government and a profit-maximizing firm. The former imposes the state of technology, some value of rent extraction, labor-market rigidities and time preference. The firm, conditional on these factors and the optimally-determined inflation rate, sets labor demand. Given its extractive nature, there is a continuous probability of a political regime shift, characterized by a hazard function (we compare state and non state contingent forms). The model is able to rationalize the early growth and developmental gains of many Arab economies and their subsequent reversal, as well as the later stalling of economic reforms. The model provides a novel analysis of the evolution of the Arab economies, the shifting time preferences of policy makers and their interaction with economic reforms. Highlights: Following Arab Spring, we examine macroeconomic stabilization under regime shift. Model is a dynamic interaction between a government and a profit-maximizing firm. Continuous probability of a regime shift, characterized by a hazard function. We rationalize the early growth gains of Arab economies and later reversal.